Implikasi Hukum bagi Notaris yang Menghindari Panggilan Penyidik - Ghuto, Ilham Prabowo; Ruslijanto, Patricia Audrey; Wisnu Wardani, Diah Aju (JURNAL USM LAW REVIEW, 2024)
This study aims to analyze and examine the legal sanctions imposed on notaries who disregard the provisions of Article 66 paragraph (1) of Law Number 2 of 2014 on the Notary Position regarding being summoned by investigators to attend examinations concerning deeds they have drafted. Notaries play a crucial role as public officers in creating authentic legal documents and maintaining the confidentiality of information, with certain legal protections that require approval from the Regional Notary Honor Council before they can be summoned as witnesses by investigators or prosecutors. The urgency of this research lies in the need to clarify the legal consequences for notaries who violate these summoning rules. This research employs a normative legal methodology using legislative and conceptual approaches to study legal norms and incidents. Primary, secondary, and tertiary legal sources serve as the information bases. Descriptive, grammatical, and systematic interpretation is used as analytical tools to reveal the norms concerning the issues studied. Therefore, the novelty of this research is providing an in-depth analysis of legal sanctions for notaries who fail to follow the mandated summoning procedures, filling a gap in legal literature, and offering recommendations for policy reform. The findings of this study indicate that the ambiguity of norms and the gaps in legal regulations regarding the examination of notaries by investigators without permission from the Notary Honor Council can pose significant legal risks and inconsistencies in law enforcement. Thus, it is crucial to revise and clarify the regulations concerning the examination of notaries, including the mechanism for obtaining permission from the Notary Honor Council, to ensure legal certainty and avoid normative ambiguity that could affect the integrity of the notary profession and the judicial process.Tujuan penelitian ini mengаnalisis dаn mengkаji pengenaan sаnksi hukum bаgi notаris yаng mengabaikan ketentuan Pаsal 66 ayat (1) Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan Notaris terkаit pemanggilаn oleh penyidik untuk hаdir dаlam pemeriksаan atаs аkta yаng dibuatnyа. Notaris memiliki peran penting sebagai pejabat publik dalam menciptakan dokumen hukum autentik dan menjaga kerahasiaan informasi, dengan perlindungan hukum tertentu yang mengharuskan persetujuan dari Majelis Kehormatan Notaris Wilayah sebelum mereka bisa dipanggil sebagai saksi oleh penyidik atau penuntut. Urgensi penelitian ini terletak pada perlunya memperjelas konsekuensi hukum untuk Notaris yang melanggar aturan pemanggilan penyidik. Untuk mengkaji norma-norma hukum dan kejadian-kejadian hukum, penelitian ini menggunakan metodologi hukum normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Sumber hukum primer, sekunder, dan tersier merupakan sumber informasi hukum. Interpretasi deskriptif kualitatif, gramatikal, dan sistematis digunakan sebagai alat analisis untuk mengungkap norma-norma permasalahan yang diteliti. Maka kebaharuan penelitian ini adalah menyediakan analisis mendalam tentang sanksi hukum bagi Notaris yang tidak mengikuti prosedur pemanggilan yang diwajibkan, mengisi celah dalam literatur hukum dan menawarkan rekomendasi untuk reformasi kebijakan. Hasil penelitian ini menunjukkan bahwa ketidakjelasan norma dan kekosongan dalam regulasi hukum mengenai pemeriksaan Notaris oleh penyidik tanpa izin dari Majelis Kehormatan Notaris dapat menimbulkan risiko hukum yang signifikan dan inkonsistensi dalam penegakan hukum. Dengan demikian pentingnya merevisi dan memperjelas peraturan yang mengatur tentang pemeriksaan Notaris, termasuk mekanisme pengambilan izin dari Majelis Kehormatan Notaris, untuk memastikan kepastian hukum dan menghindari kekaburan norma yang dapat mempengaruhi integritas profesi Notaris serta proses peradilan.